Personalized digital intervention for depression based on social rhythm principles adds significantly to outpatient treatment - Frank, Ellen; Wallace, Meredith L.; Matthews, Mark J.; Kendrick, Jeremy; Leach, Jeremy; Moore, Tara; Aranovich, Gabriel; Choudhury, Tanzeem; Shah, Nirav R.; Framroze, Zeenia; Posey, Greg; Burgess, Samuel A.; et al. (Frontiers in Digital Health, 2022)
We conducted a 16-week randomized controlled trial in psychiatric outpatients with a lifetime diagnosis of a mood and/or anxiety disorder to measure the impact of a first-of-its-kind precision digital intervention based on social rhythm regulation principles (Cue). The full intent-to-treat (ITT) sample consisted of 133 individuals, aged 18 – 65. The primary sample of interest were individuals with moderately severe to severe depression at study entry (baseline PHQ-8 score ≥15; N=28). Cue is a novel digital intervention platform that capitalizes on the smartphone’s ability to continuously monitor depression-relevant behavior patterns and use each patient’s behavioral data to provide timely, personalized ‘micro-interventions,’ making this the first example of a digital precision intervention that we are aware of. Participants were randomly allocated to receive Cue plus care-as-usual or digital monitoring only plus care-as-usual. Within the depressed and full ITT samples, we fit a mixed effects model to test for group differences in the slope of depressive symptoms over 16 weeks. To account for the non-linear trajectory with more flexibility, we also fit a mixed effects model considering week as a categorical variable and used the resulting estimates to test the group difference in PHQ change from baseline to 16 weeks. In the depressed-at-entry sample, we found evidence for benefit of Cue. The large group difference in the slope of PHQ-8 (Cohen’s d= -0.72) indicated a meaningfully more rapid rate of improvement in the intervention group than in the control group. The Cue group also demonstrated significantly greater improvement in PHQ-8 from baseline to 16 weeks (p=0.009). In the full sample, the group difference in the slope of PHQ-8 was negligible (Cohen’s d=-0.10); however, the Cue group again demonstrated significantly greater improvement from baseline to 16 weeks (p=0.040). We are encouraged by the size of the intervention effect in those who were acutely ill at baseline, and by the finding that across all participants – 80% of whom were receiving pharmacotherapy - we observed significant benefit of Cue at 16 weeks of treatment. These findings suggest that a social rhythm-focused digital intervention platform may represent a useful and accessible adjunct to antidepressant treatment.